Steaming into history : liberty ship John W. Brown in convoy - 1944 - Brett, Oswald, 1921-2017; Project Liberty Ship ([Baltimore, Md.] : published by Project Liberty Ship, 1997)
Poster of the U.S. WWII liberty ship John. W. Brown. The poster features an image of the John W. Brown in convoy, 1944, with other liberty ships behind it and additional naval vessels travelling to the right of the liberty ships. The image is signed "Oswald Brett '97" in the waves at the foot of the image. The poster was published "in conjunction with the publication of "Liberty Ship: The Voyages of the John W. Brown, 1942-1946" by Dr. Sherod Cooper."
Caption title.
National Library of Australia's copy signed by the artist "Oswald L. Brett, Eastwood, N.S.W., Jan. 11, 1998." Library's copy also has a pencil sketch below the printed image - labelled "N.Y. Harbour" the sketch shows the Liberty Ship John W. Brown with the Statue of Liberty in the background. A brief history of the John W. Brown appears in the artist's hand on the reverse.
Digital master available
Keywords: John W. Brown (Ship) -- Posters; World War, 1939-1945 -- Naval operations, American -- Posters; Liberty ships -- America -- Posters; Posters, Australian; Australian